Gold Nanoparticle–Decorated Earth-Abundant Clay Nanotubes as Catalyst for the Degradation of Phenothiazine Dyes and Reduction of 4-(4-Nitrophenyl)Morpholine - Singh, D (Springer, 2023)
In the present work, halloysite nanotubes modified with gold nanoparticles (AuNPs-HNT) are successfully prepared by wet chemical method for the catalytic degradation of phenothiazine dyes (azure B (AZB) and toluidine blue O (TBO)) and also cleaner reduction of 4-(4-nitrophenyl)morpholine (4NM) in the sodium borohydride (NaBH4) media. The catalyst is formulated by modifying the HNT support with a 0.964% metal loading using the HNT supports modified with 3-aminopropyl-trimethoxysilane (APTMS) coupling agent to facilitate the anchoring sites to trap the AuNPs and to prevent their agglomeration/aggregation. The AuNPs-HNT catalyst is investigated for structural and morphological characterization to get insights about the formation of the catalyst for the effective catalytic reduction of dyes and 4NM. The microscopic studies demonstrate that AuNPs (2.75 nm) are decorated on the outer surface of HNT. The as-prepared AuNPs-HNT catalyst demonstrates AZB and TBO dye degradation efficiency up to 96% in 10 and 11 min, respectively, and catalytic reduction of 4NM to 4-morpholinoaniline (MAN) is achieved up to 97% in 11 min, in the presence of NaBH4 without the formation of any by-products. The pseudo-first-order rate constant (K1) value of the AuNPs-HNT catalyst for AZB, TBO, and 4NM were calculated to be 0.0078, 0.0055, and 0.0066 s−1, respectively. Moreover, the synthesized catalyst shows an excellent reusability with stable catalytic reduction for 7 successive cycles for both the dyes and 4NM. A plausible mechanism for the catalytic dye degradation and reduction of 4NM by AuNPs-HNT catalyst is proposed as well. The obtained results clearly indicate the potential of AuNPs-HNT as an efficient catalyst for the removal of dye contaminants from the aquatic environments and cleaner reduction of 4NM to MAN, insinuating future pharmaceutical applications. © 2022, The Author(s), under exclusive licence to Springer-Verlag GmbH Germany, part of Springer Nature.